Rationale and design of the Baptist Employee Healthy Heart Study: a randomized trial assessing the efficacy of the addition of an interactive, personalized, web-based, lifestyle intervention tool to an existing health information web platform in a high-risk employee population. Issue 1 (December 2016) - Post, Janisse; Ali, Shozab; Roberson, Lara; Aneni, Ehimen; Shaharyar, Sameer; Younus, Adnan; Jamal, Omar; Ahmad, Rameez; Aziz, Muhammad; Malik, Rehan; Spatz, Erica; Feldman, Theodore; et al.
Abstract Background Metabolic syndrome (MetS) and diabetes confer a high risk for developing subsequent cardiovascular disease (CVD). Persons with MetS constitute 24–34 % of the employee population at Baptist Health South Florida (BHSF), a self-insured healthcare organization. The Baptist Employee Healthy Heart Study (BEHHS) aims to assess the addition of a personalized, interactive, web-based, nutrition-management and lifestyle-management program to the existing health-expertise web platform available to BHSF employees in reducing and/or stabilizing CVD and lifestyle risk factors and markers of subclinical CVD. Methods/design Subjects with MetS or Type II Diabetes will be recruited from an employee population at BHSF and randomized to either an intervention or a control arm. The intervention arm will be given access to a web-based personalized diet-modification and weight-modification program. The control arm will be reminded to use the standard informational health website available and accessible to all BHSF employees. Subjects will undergo coronary calcium testing, carotid intima-media thickness scans, peripheral arterial tonometry, and advanced lipid panel testing at visit 1, in addition to lifestyle and medical history questionnaires. All tests will be repeated at visits 2 and 4 with the exception of the coronary calcium test, which will only be performed at baseline and visit 4. Visit 3 will capture vitals, anthropometrics, and responses to the questionnaires only. Conclusion Results of this study will provide information on the effectiveness of personalized, web-based, lifestyle-management tools in reducing healthcare costs, promoting healthy choices, and reducing cardiovascular risk in an employee population. It will also provide information about the natural history of carotid atherosclerosis and endothelial dysfunction in asymptomatic but high-risk populations. Trial registration ClinicalTrials.gov registry, NCT01912209 . Registered on 3 July 2013.